If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3 = 0 Reorder the terms: 3 + 2y = 0 Solving 3 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 0 + -3 2y = 0 + -3 Combine like terms: 0 + -3 = -3 2y = -3 Divide each side by '2'. y = -1.5 Simplifying y = -1.5
| t+3-3.2=3 | | 48=8.21*t | | 7u+5-4(-3u-1)=3(u-1) | | 48=.512n | | 11x^2+22x=0 | | t+6-3.2=3 | | 9*-8= | | n-13=15 | | -6m^2+5m+2=0 | | 11-3(4+a)=2a | | -5a-1=1-5a | | t^2-4=12 | | 2x^3+8x^2+10x+4=0 | | -5(x+8)=4-x | | -2v+8=8-8v+6v | | 6m^2-5m-2=0 | | 6x+2x=20x | | -12(-4)-(-3)= | | .75n-3=9 | | 14x^2+6x-8=0 | | 4(2x+4)=20 | | 4(a+3)=18-3(3-2a) | | 3x-5x+10=2 | | 2(y+3)=14 | | t+5.5=21 | | n+16=18 | | 7p-(3p+4)=-2(2p-1) | | 0.25x^4-2x^2+3x-1.25=0 | | 5(4c-1)-6=18c+3 | | 6=3x | | 10x+12=4x+114 | | 3t+24=16 |